Kashmir Basin Fault and its tectonic significance in NW Himalaya, Jammu and Kashmir, India - Shah, Afroz Ahmad (Springer, 2015)
The Kashmir Basin Fault is located in the Jammu and Kashmir region of Kashmir Basin in NW Himalaya, India. It is a classic example of an out-of-sequence thrust faulting and is tectonically active as observed from multiple geological evidences. Its geomorphology, structure and lateral extent indicate significant accommodation of stress since long, which is further supported by the absence of a large earthquake in this region. It seems this fault is actively accommodating some portion of the total India–Eurasia convergence, apart from two well-recognised active structures the Medlicott–Wadia Thrust and the Main Frontal Thrust, which are referred in Vassallo et al. (Earth Planet Sci Lett 411:241–252, 2015). This requires its quantification and inclusion into slip distribution scheme of NW Himalaya. Therefore, it should be explored extensively because this internal out-of-sequence thrust could serve major seismic hazard in KB, repeating a situation similar to Muzaffarabad earthquake of Northern Pakistan in 2005. © 2015, Springer-Verlag Berlin Heidelberg.